Flocculation of rubber factory wastewater - Nkwekam N M; Kayem G J; Ndi K S (Journal of Rubber Research, 2016)
Coagulation/flocculation of rubber latex wastewater was studied with two types of polymers. Experiments were carried out in a jar test using a long chain (FO 8650) and a short chain cationic polyacrylamide (U 5000). Influence of rubber concentration on polymer demand, amount of rubber recovered, and residual turbidity was studied. This is in addition to the study of the influence of wastewater initial pH on polymer demand and flocculation kinetics. The results showed that flocculation with FO 8650 and U 5000 could recover up to 98;of the rubber in suspension in about 60 min of clarification. Polymer dose (mg/L) increased with increasing rubber concentration while the polymer demand (mg/g rubber) decreased with increasing rubber concentration at low suspension concentration. The amount of rubber recovered was independent on the rubber concentration at the optimum polymer dose. Whilst the polymer demand increased with increasing pH flocculation, performance was found to be independent of pH at the optimum polymer dose. Residual turbidity of clarified wastewater at the optimum polymer dose and clarification time was<_12 NTU.
Source Year: 2016
Keywords: Coagulation; Flocculation; Latex; Pollution abatement; Polyacrylamide